Qualitative Analysis of Instructional Strategies That Integrate Assessment and Learning Goals - Nabavifar, Haleh; Kalhor, Mojtaba (Assessment and Practice in Educational Sciences, 2024)
This study aimed to explore the instructional strategies employed by teachers to effectively integrate assessment with learning goals in classroom practice. A qualitative research design was adopted using semi-structured interviews with 14 educators from secondary and higher education institutions in Tehran. Participants were purposefully selected based on their involvement in curriculum design and assessment practices. Data were collected until theoretical saturation was achieved. All interviews were transcribed verbatim and analyzed using thematic analysis, assisted by NVivo software. Thematic coding focused on identifying patterns related to pedagogical alignment, student-centered strategies, and institutional enablers of integration. Three overarching themes emerged from the data: pedagogical alignment, learner-centered strategies, and institutional and contextual enablers. Participants reported aligning assessments with clearly defined learning objectives through backward design, embedded checkpoints, and continuous monitoring. They also emphasized student agency through co-construction of goals, feedback for growth, and peer assessment. Additionally, professional development, supportive leadership, and collaborative school cultures were identified as essential for sustaining integrated practices. Teachers highlighted the challenges of rigid curriculum mandates and limited resources but demonstrated a strong commitment to formative, responsive assessment practices tailored to student needs. The findings highlight the pedagogical depth with which teachers approach the integration of assessment and learning goals. Effective alignment relies not only on technical assessment design but also on reflective instructional planning and institutional support. The study underscores the importance of professional development, leadership engagement, and collaborative environments in enabling sustainable formative assessment practices. These insights contribute to a deeper understanding of assessment as a dynamic instructional tool that fosters student learning and engagement.